Extra-Corporeal Membrane Oxygenation Cadaver Donors: What about Tissues Used as Allografts? - Gregorio Marchiori; Matteo Berni; Giorgio Cassiolas; Leonardo Vivarelli; Nicola Francesco Lopomo; Milena Fini; Dante Dallari; Marco Govoni (Membranes, 2021)
Several studies demonstrated the efficacy of post-mortem extracorporeal membrane oxygenation (ECMO) on donors in preserving organ function addressing organ transplantation. Nevertheless, no common and shared evidence was reached about the possibility of using ECMO donors in tissue harvesting. Therefore, this work aimed first to review the current scientific literature about ECMO donors, and then to focus on the use of ECMO tissues as allografts, mainly addressing musculoskeletal tissues, which are of the most interest for reconstruction. A search was conducted on the current scientific literature, focusing on the keywords “ECMO” and “Donor”. Several online databases were used, including PubMed, Scopus, and Web of Science. From the preliminary search, 478 articles were obtained, out of which 173 specifically reported the use of ECMO for donation and transplantation purposes. Literature reported extensive analyses of ECMO organs—overall from the abdomen—both in pre- and post-transplantation studies. On the other hand, ECMO tissues were explanted only in a very limited number of cases; moreover, no information was referred about their status and use. A revision of the current scientific literature highlighted the lack of information concerning ECMO tissues and the necessity to perform preclinical, ex vivo studies to compare allografts from ECMO donors, with respect to standard donors, and, thus, to verify whether they can be harvested and implanted safely and with efficacy.